Reartikulasi Amar Ma’ruf Nahi Munkar sebagai Konseling Sosial Emansipatoris: Fondasi Teologi Transformatif Anti-Penindasan - Nayla Nurfadillah; Muh. Hamidi; Ali Hasan (Jurnal Teologi Islam, 2026)
The Rearticulation of Amar Ma’ruf Nahi Munkar as Emancipatory Social Counseling: Toward a Transformative Anti-Oppression Theology. This article examines the rearticulation of amar ma’ruf nahi munkar as an emancipatory social counseling paradigm grounded in transformative anti-oppression theology. The study is motivated by the tendency to interpret amar ma’ruf nahi munkar primarily as an instrument of individual moral control, limiting its potential as a framework for addressing structural injustice and social oppression. The objective of this study is to analyze the concept of amar ma’ruf nahi munkar from the perspective of transformative Islamic theology and to formulate a prophetic-emancipatory counseling model that integrates theological, psychological, and sociological dimensions. This research employs a qualitative approach based on library research using a critical-hermeneutic method. Data sources include the Qur’an, Hadith, classical exegetical works, Sufi and Islamic philosophical literature, as well as contemporary academic publications relevant to the topic. The analysis is conducted through textual interpretation, contextual analysis, and conceptual reconstruction. The findings reveal that amar ma’ruf nahi munkar possesses significant potential as a mechanism of critical consciousness that encourages both personal transformation and social change. The integration of divine values, self-awareness, and collective action produces a prophetic-emancipatory counseling model characterized by dialogue, participation, and liberation-oriented transformation. The novelty of this article lies in repositioning amar ma’ruf nahi munkar from a normative moral doctrine into a social counseling framework capable of linking religious reflection, the internalization of prophetic values, and social transformation within the broader discourse of transformative anti-oppression theology.